Low-Intensity Whole-Body Vibration: A Useful Adjuvant in Managing Obesity? A Pilot Study - Michele Gobbi; Cristina Ferrario; Marco Tarabini; Giuseppe Annino; Nicola Cau; Matteo Zago; Paolo Marzullo; Stefania Mai; Manuela Galli; Paolo Capodaglio (Applied Sciences, 2021)
The use of whole-body vibration (WBV) for therapeutic purposes is far from being standardized and an empirical foundation for reporting guidelines for human WBV studies has only very recently been published. Controversies about safety and therapeutic dosage still exist. The present study aimed to investigate the metabolic and mechanical effects of low-intensity WBV according to the ISO 2631 norm on subjects with obesity. Forty-one obese subjects (BMI ≥ 35 kg/m2) were recruited to participate in a 3-week multidisciplinary inpatient rehabilitation program including fitness training and WBV training. During WBV the posture was monitored with an optoelectronic system with six infrared cameras (Vicon, Vicon Motion System, Oxford, UK). The primary endpoints were: variation in body composition, factors of metabolic syndrome, functional activity (sit-to-stand and 6-min walking test), muscle strength, and quality of life. The secondary endpoints were: modification of irisin, testosterone, growth hormone, IGF1 levels. We observed significant changes in salivary irisin levels, Group 2 (p < 0.01) as compared to the control group, while muscle strength, function, and other metabolic and hormonal factors did not change after a 3-week low-intensity WBV training with respect to the control group. Future studies are needed to further investigate the potential metabolic effect of low-intensity WBV in managing weight.